The Occupational Transformation of Coastal Fishers in Advancing Coastal Economic Sustainability: A Case Study in Sanur, Bali - Made Ika Prastyadewi; Putu Yusi Pramandari; I Gusti Lanang Putu Tantra; Agung Budi Leksono Prastyadewi (Jurnal Ekonomi dan Bisnis Jagaditha, 2026)
The increase of economic and environmental pressures in coastal areas have caused many fishermen to switch from traditional livelihoods to the tourism sector. This study aims to analyze the factors that influence the transformation of traditional fishermen's jobs in the coastal area of Sanur, Bali, in the context of sustainable tourism development. A quantitative approach using logistic regression was used to analyze the relationship among socio-demographic, economic, and tourism factors and the decision to change occupations. The results imply that higher levels of education, ownership of tourism-related assets, and more intense interaction with the tourism environment increase the likelihood of fishermen transforming their occupations. Conversely, older fishermen tend to be more resistant to changing their traditional livelihoods. These findings emphasize the importance of social and economic readiness in supporting sustainable transitions in the coastal economy. This research contributes to the transformation of economic structures and economic development, which in turn has policy implications on the formulation of community-based tourism policies.